ASSOCIATION BETWEEN THORACIC KYPHOSIS, HEAD POSTURE AND CERVICAL RANGE OF MOTION IN ADULTS WITH AND WITHOUT CERVICAL SPINE DYSFUNCTION (International Journal of Physiotherapy, 2016)
Background: Excessive Thoracic Kyphosis (TK) and Forward Head Posture(FHP) become more apparent in aging adults from the accumulation of remodeling in response to habitual postures. Faulty posture of the shoulders, neck, and particularly the head may contribute to the onset and perpetuation of cervical pain dysfunction syndrome. Current literature suggests that an association exists between the head posture, thoracic kyphosis and cervical range of motion in individuals with cervical spine dysfunction. Since age as well as cervical spine dysfunction may affect the above parameters, the objective of our research was to study the association between these in adults with and without cervical spine dysfunction.Methods: 50 adults with CSD and 50 adults without CSD were assessed for TK, FHP and Cervical range of motion (CROM) by flexicurve method Kipnotic Index (KI), measuring cranio-vertebral angle(CVA) using a lateral-view photograph(digitized) of the subject and using Universal Goniometer respectively.Results: In both groups, there was increased KI (TK), lesser CVA i.e. FHP and reduced CROM when compared to normative values, however there was no statistical difference in KI and CVA between the two groups (p=0.53,0.75). Cervical extension and rotation ranges were significantly reduced in CSD adults (p=0.00,0.00,0.00). Correlation between CVA and CROM, KI and CROM and KI and CVA was not significant in adults with as well as without CSD (p=0.16-0.51,0.05-0.35,p=0.08-0.69,0.19-0.52,p=0.13,0.94 respectively).Conclusion: Correlation between FHP and CROM,TK and CROM, FHP and TK in adults with and without CSD was not significant.